Efficacy and safety of cryoballoon ablation versus radiofrequency catheter ablation in atrial fibrillation: an updated meta-analysis - Ma, Honglan; Sun, Dongdong; Luan, Hui; Feng, Wei; Zhou, Yaqiong; Wu, Jine; He, Caiyun; Sun, Chaofeng (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: Cryoballoon ablation (CBA) and irrigated radiofrequency catheter ablation (RFCA) are the main treatments for drug-refractory symptomatic atrial fibrillation (AF). Aim: To compare the efficacy and safety between CBA and RFCA for the treatment of AF. Material and methods : We searched the Embase and Medline databases for clinical studies published up to December 2016. Studies that satisfied our predefined inclusion criteria were included. Results : After searching through the literature in the two major databases, 20 studies with a total of 9,141 patients were included in our study. The CBA had a significantly shorter procedure time (weighted mean difference (WMD) –30.38 min; 95% CI: –46.43 to –14.33, p = 0.0002) and non-significantly shorter fluoroscopy time (WMD –3.18 min; 95% CI: –6.43 to 0.07, p = 0.06) compared with RFCA. There was no difference in freedom from AF between CBA and RFCA (CBA 78.55% vs. RFCA 83.13%, OR = 1.15, 95% CI: 0.95–1.39, p = 0.14). The CBA was associated with a high risk of procedure-related complications (CBA 9.02% vs. RFCA 6.56%, OR = 1.56, 95% CI: 1.05–2.31, p = 0.03), especially phrenic nerve paralysis (PNP, OR = 10.72, 95% CI: 5.59–20.55, p < 0.00001). The risk of pericardial effusions/cardiac tamponade was low in the CBA group (CBA 1.05% vs. RFCA 1.86%, OR = 0.62, 95% CI: 0.41–0.93, p = 0.02). Conclusions : For AF, CBA was as effective as RFCA. However, CBA had a shorter procedure time and a non-significantly shorter fluoroscopy time, a significantly high risk of PNP and a low incidence of pericardial effusions/cardiac tamponade compared with RFCA.